(untitled) (Bangladesh Journal of Medical Science, 2016)
Introduction: Autoimmune phenomenon is attributed to a number of diseases which were once considered idiopathic. In humans, production of auto antibodies (a-Abs) against self-antigens is quite frequent but earlier their presence was associated with autoimmune diseases, however a-Abs have been documented in non-autoimmune disorders i.e. complicated pregnancy, cancer, stroke etc. In Pakistan, limited data is available on frequency of a-Abs, therefore this study was designed to determine serum level of antinuclear antibody (ANA), Rheumatoid factor (RF) and anti dsDNA antibodies in apparently healthy population. Materials and methods: After written informed consent, blood sample of 256 subjects was obtained by random sampling. Participants of established autoimmune diseases were excluded. Enzyme linked immunosorbent assay (ELISA) was used to determine ANA, RF and anti-dsDNA antibody. Categorical variables were compared by using c2 test. A p value <0.05 was considered statistically significant. Results: Rheumatoid factor was the most frequent a-Ab (18%), followed by anti dsDNA (7.4%), while ANA was the lowest (0.4%) antibody detected. Only RF had a statistically significant association with gender (p=0.047). No association of these antibodies with age was detected. Conclusion: Rheumatoid factor auto antibody was more prevalent as compared to ANA and dsDNA antibody in healthy adults. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.579-582